Constitutionality of President’s Authority Regarding Lockdown Policy During the State’s Emergency - Wahid, Deny Noer; Ramadhan, Febriansyah; Utami, Tasyabilla Pandi (Faculty of Law Universitas Negeri Semarang, 2022)
The Article 22 of the 1945 Constitution of the Republic of Indonesia grants an exclusive authority to the president enacted as